THE IMPACT OF SELF-ESTEEM ON THE DEGREE OF GENERAL AND EXAMINATION ANXIETY - Georgievska, Sofija (Ревија за социјална политика/Journal of Social Policy, 2015)
The purpose of this research was to clarify the relationship to thelevel of self esteem and general and examination anxiety, as well as todetermine the difference between general and examination anxiety amongthe students. Measuring instruments that were used in this research areRosenberg self-esteem Scale, anxiety scale constructed by Hamilton andTest Anxiety Inventory (TAI).